The Effect of Gamification Learning Model to Improve Students' Critical Thinking Skills in Elementary School Science and Social Subjects - Wibisono, Fajar Citra; Wahyudin, D; Yogiarni, Tiara (MID Publisher International, 2024)
This study aims to examine the effect of gamification learning model on improving students' critical thinking skills in Natural and Social Sciences (NSP) subjects in elementary schools. The research method used was pre-experiment with pretest-posttest research design. The research sample used one class as an experimental group that used the gamification learning model. The research instrument used to measure students' critical thinking skills is a validated critical thinking test. The results of data analysis showed that there was a significant increase in students' critical thinking skills in the experimental group. This finding indicates that the application of gamification learning model can effectively improve students' critical thinking skills in IPAS learning in elementary school. Therefore, the use of gamification in the learning process is suggested as one of the strategies to improve the quality of education and students' critical thinking skills.